EFFECT OF IMPROVAL ON SOME PRODUCTIVE AND EGG QUALITY TRAITS IN VANARAJA CHICKEN (Indian Journal of Animal Production and Management, 2014)
An experiment was conducted to evaluate the response of laying Vanaraja hens to dietary supplementation of probiotic (Improval) for 7 months. A total of 200 Vanaraja layers at 24 weeks of age were randomly divided into two groups with four replicates of 25 birds in each and reared in deep litter system under standard management systems. It was distinct from the results that dietary inclusions of probiotic had significant effect (P
Keywords: Probiotic; FCR; egg production; egg quality; mortality; Vanaraja hens